Matrilineal heritage and interpersonal relationship among the indigenous people of Kampung Pulo - Hidayat, Dasrun; Hamdani, Neng Heni Rachmawati; Nur Afifa, Vanessa Aura; Taufik, Reza Rizkina (Jurnal Kajian Komunikasi, 2024)
Background: The cultural practice of inheritance through the female lineage, known as matrilineal relationship, is built on the belief in inheritance values that women are more appropriate to be heirs. However, belief alone is not enough to build a shared commitment to maintain the cultural relationship of the matrilineal system. Purpose: This study aimed to analyze the process of matrilineal cultural relations in the interpersonal relationships of the indigenous people of Kampung Pulo, Garut. Methods: It employed a phenomenological study with a qualitative approach. Data was collected through observation and interviews. The participants were selected purposively with a total of 10 informants consisting of the customary head, deputy customary head, and indigenous people of Kampung Pulo, the original descendants of Embah Dalem Arief Muhammad. Result: This study shows women in the indigenous people of Kampung Pulo play a crucial role in cultural inheritance, especially in preserving heirloom property. Some aspects of interpersonal relationships strengthen matrilineal relationships among the indigenous people of Kampung Pulo. Matrilineal cultural relationships are maintained because they are believed to have values, such as togetherness, harmony, mutual respect, nurturing, and cooperation. Conclusion: The family of the indigenous people of Kampung Pulo is more harmonious with the matrilineal cultural relationship system. The culture is preserved if the members can establish good interpersonal relationships. Implication: The study results are expected to contribute to the cultural preservation in Kampung Pulo, Garut. Besides, it might be worth referring to those who research the matrilineal system, either further research related to its relationship with interpersonal relationships or other fields.